Perbedaan Kadar Kalsium Dalam Saliva Sebelum Dan Sesudah Mengkonsumsi Minuman Ringan Ringan yang mengandung asam Bikarbonat - Muhammad Ilyas; M. Yusri (DiscoverSys Inc., 2007)
The increasing consumption of soft drink has developed anxiety inhealth extraordinary in population. Many studies have showed thenegative impacts of soft drink for human health. This study aimed toknow the difference of calcium and in saliva before and afterconsumed soft drink contained bicarbonate acid. The quasiexperiment prepation time series design was conducted at BTPTlaboratory in Maros of South Sulawesi by using 5 marmots inexamination with 600 grams or over body weigth average, and 70days of age or over. Data were analyzed using SPSS versi 11 forwindows withAnova, continued with LSD test. The are different ofcalcium in saliva level before and after consumtion of soft drink whichcontain acid bicarbonate in minute 5, 10, 15, and 20 treatment withp=0.000.